PENGARUH KARAKTERISTIK INDIVIDU DAN PRESTASI KERJA TERHADAP PENGEMBANGAN KARIR PEGAWAI DI DINAS PENDIDIKAN PROPINSI RIAU - Muhammad Azmi; Hasnah Faizah; Gimin Gimin (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This study aims to investigate the influence of variables (1) the characteristicsof individuals to career development, (2) performance to career development, (3) the individualcharacteristics and job performance together to career development. Respondents wereemployees of the education department of Riau province, amounting to 163 obtained by simplerandom sampling technique. Data collected through questionnaire as a research instrument.Analysis of the data used is descriptive analysis, inferential statistical analysis and hypothesistesting. Instrument reliability coefficient is calculated using Cronbach alpha. In partial resultsshowed the positive influence between karakteristi individuals to career development amountedto 0.198, and there are positive influence between work performance on the career developmentof 0.426. While simultaneously the influence of individual characteristics and performance onthe career development of 0.573.